Evidence that the fadB gene of the fadAB operon of Escherichia coli encodes 3-hydroxyacyl-coenzyme A (CoA) epimerase, delta 3-cis-delta 2-trans-enoyl-CoA isomerase, and enoyl-CoA hydratase in addition to 3-hydroxyacyl-CoA dehydrogenase. - Yang, S Y (1988)
Genetic complementation of a mutant defective in fatty acid oxidation (fadAB) with plasmids containing DNA inserts from the fadAB region of the Escherichia coli genome was studied. The mutant containing the hybrid plasmid with a 5.2-kilobase (kb) PstI-SalI fragment was found to overproduce 3-hydroxyacyl-coenzyme A (CoA) epimerase and delta 3-cis-delta 2-trans-enoyl-CoA isomerase as well as three other beta-oxidation enzymes by 16- to 18-fold compared with the wild-type parental strain LE392. The purification of a fully functional multienzyme complex of fatty acid oxidation from the transformant ultimately established that the 5.2-kb DNA fragment contained an entire fadAB operon. Since immunotitration of cell extracts with antibodies against the fatty acid oxidation complex proved that all 3-hydroxyacyl-CoA epimerase and delta 3-cis-delta 2-trans-enoyl-CoA isomerase activities were associated with the complex, no genetic loci other than the fadAB operon encoded these two enzymes. Moreover, the binding of antibodies caused parallel inhibition of four component enzymes, whereas 3-ketoacyl-CoA thiolase activity was slightly increased. These findings support the suggestion that the epimerase and isomerase as well as enoyl-CoA hydratase and L-3-hydroxyacyl-CoA dehydrogenase are located on the same polypeptide. The results of this study, together with published data (S.-Y. Yang and H. Schulz, J. Biol. Chem. 258:9780-9785, 1983), lead to the conclusion that 3-hydroxyacyl-CoA epimerase, delta 3-cis-delta 2-trans-enoyl-CoA isomerase, and enoyl-CoA hydratase in addition to 3-hydroxyacyl-CoA dehydrogenase are encoded by the fadB gene.